BIO-ALGAL GAS CLEANING PLANT FOR TREATMENT OF BLAST FURNACE WASTEWATER - Bose, Abhishek; Bhattacharjee, Korok (MATTER: International Journal of Science and Technology, 2015)
The perennial problem is of treating harmful effluents from metallurgical processes is an interesting field of environmental innovation. A number of metallurgical industries utilize a lot of water for processes such as leaching, floatation, extraction and washing purposes. These wastewater effluents are different from other wastes as they contain salts of heavy metals, complex compounds and cyanides which have been found to be very harmful to the environment. Blast furnaces primarily use water to wash down waste materials from the ore after processing. This wastewater mainly contains dissolved salts, suspended solids, cyanides, chlorides, ammonia and trace amounts of other contaminants. A novel pathway for treatment of this blast furnace wash water is being suggested which utilizes microbial action on these compounds to break them down into harmless compounds which can be easily removed from the effluent stream. Cyanides and ammonia are the major pollutant which is being treated with microbial activity. The proposed pathway also allows harvesting biomass which can be used for the auxiliary production of biofuels from wastewater treatment.